Encryption : toward secure systems (O'Reilly Media, 2016)
"Software developers world-wide place a great deal of trust in the encryption technologies used to protect privacy and sensitive data. What could go wrong? Plenty, says security and encryption expert Brian Sletten in this wide ranging overview of the history, methods, technologies, goals, and perhaps most importantly, limitations of encryption. The video offers a high level discussion of the theories behind encryption as well as a lower level detailed explanation of the technologies and methods used in encryption today."--Resource description page.